2015
DOI: 10.1016/j.jvs.2015.06.218
|View full text |Cite
|
Sign up to set email alerts
|

Increasing efficacy of endovascular recanalization with covered stent graft for TransAtlantic Inter-Society Consensus II D aortoiliac complex occlusion

Abstract: At 2 years of follow-up, the results of endoluminal bypass grafting with the Viabahn stent to treat complex aortoiliac disease are promising. Longer-term results are needed to fully evaluate the potential benefits and longer-term patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 24 publications
1
24
0
1
Order By: Relevance
“…In particular, for long occlusions a CS was preferred, because it allows flow restoration creating a new endo-conduit from healthy to healthy vessels (from the aorta to the femoral artery), mimicking the concept of the traditional aorto-bifemoral bypass. This technical choice is corroborated by the excellent results obtained by Psacharopulo et al, 12 which demonstrated similar 2 year primary patency using this approach compared with standard open repair (91% vs. 95%).…”
Section: Discussionmentioning
confidence: 55%
“…In particular, for long occlusions a CS was preferred, because it allows flow restoration creating a new endo-conduit from healthy to healthy vessels (from the aorta to the femoral artery), mimicking the concept of the traditional aorto-bifemoral bypass. This technical choice is corroborated by the excellent results obtained by Psacharopulo et al, 12 which demonstrated similar 2 year primary patency using this approach compared with standard open repair (91% vs. 95%).…”
Section: Discussionmentioning
confidence: 55%
“…Interestingly, in a study by Humphries et al 7 in 2014 looking strictly at percutaneous iliac artery interventions, the use of covered balloon-expandable stents conferred a reduction in patency rates compared with bare-metal balloon-expandable stents. In two separate series by Piazza et al 8 and Psacharopulo et al, 9 it was demonstrated that covered stents for severe iliac lesions had patency rates similar to those of bare-metal stents. However, when both of these groups of investigators looked specifically at long-segment TASC D lesions, covered stents actually had better patency rates than baremetal stents in this subgroup of patients.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, open reconstructionsare related to higher operative morbidity, mortality [11,12], length of hospital stay [9,13] and short-term costs [14]. Evaluating percutaneous treatment, the risks of renal insufficiency, embolization and access complications are not insignificant; however, they can be prevented or managed without significant clinical consequence.…”
Section: Case Journal Of Case Reports and Studiesmentioning
confidence: 99%
“…In some situations, due to anatomic considerations or clinical risks, an axillo-bifemoral or a unilateral axillo-femoral/aorto-femoralbypass with a femoro-femoral crossover may be used. Long-term primary patency rates for open bypass are undoubtedly superior to endovascular intervention [9]; however, secondary patency rates are comparable [5][6][7]10].…”
Section: Introductionmentioning
confidence: 99%